TEA: A JOURNEY FROM THE EAST TO MIDATLANTIC - Mário Moura (European Scientific Journal, ESJ, 2015)
In this paper, we will focus on the tea journey from his Chinese birthplace to Azores, in Europe. We will approach it in a global, transcontinental and transoceanic way. 1 Along with coffee, cotton, potatoes, cocoa and sugar-cane, tea has changed - socially and economically -, the world’s landscape. To understand this specific journey, one has to travel back and forth in time. Thus, we hope to understand tea, first, as a trade commodity sold to the Europeans by Chinese and Japanese, next, as a trade commodity manufactured and sold by some European countries. We will emphasize the Azorean case. As we classed Azorean Tea History in eleven time periods 2 , this present study falls into the long time period before 1801: ‘1.º Time: From spontaneity to early tries’ 3 . While then we had divided that period into three different moments, due to additional data, now we add a fourth moment: from the 1860’s to 1873.